(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Purpose: The midfacial degloving approach (MFDA) is the primary option for surgical treatment of midface lesion. Usually most benign and malignant paranasal sinus (PNS) tumours are unilateral. So the classic MFDA does not fit for every case. Modifications of the classical MFDA are then tailored accordingly for surgical field exposure to achieve the goal. MFDA was first suggested by Portmann in 1927, but the modern technique had its origin in 1974 with the report by Casson and colleagues. It was not until Conley and Price first suggested that the technique be used for the excision of neoplastic disease in 1979 that its use was fully realized. It can be of great benefit for the management of various lesions, mainly tumors, of the facial cavities, paranasal sinuses, nasopharynx, orbits, and central compartment of the anterior and middle cranial fossae, allowing adequate bilateral maxillary and lower nasal cavity exposure without cosmetic dysfunction. Patients: A male patient of 20 years was admitted with history of faciomaxillary trauma having significant external deformity. Under GA open rhinoplasty and reduction & immobilization of fractured segments were done with adequate exposure of midface using midfacial degloving procedure. Result: We have performed MFDA in one case only for the first time. Utilizing sublabial gingivobuccal incision, a complete transfixion incision, intercartilaginous incision with mucosal detachment of the pyriform aperture nasomaxillary skeleton along with zygoma were exposed adequately. No technical problems and no intraoperative complications related to the surgical procedure were encountered. Cosmetic outcome was also satisfactory. Conclusion: Midfacial degloving can be considered as an excellent, useful, and safe approach for many lesions of the midface that has a low complication rate with excellent cosmetic outcomes. It provides excellent exposure to the midportion of the craniofacial skeleton, yet avoids external incisions and should be in every head and neck surgeons armamentarium. Bangladesh J Otorhinolaryngol; April 2015; 21(1): 51-56